PEMBERDAYAAN MAHASISWA POLTEKKES KEMENKES MALANG DAN ANAK PANTI ASUHAN SUNAN AMPEL MELALUI WIRAUSAHA PRODUK KREATIF HASIL OLAHAN BUAH APEL MANALAGI AFKIR - Dumilah, Retno; Rahman, Nur; Apsari, Duhita Dyah; Marcelina, Sheila Tania (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2025)
The Health Polytechnic of the Ministry of Health of Malang, as one of 38 Health Polytechnics of the Ministry of Health in Indonesia, has an important role in developing student entrepreneurship, but there has been no maximum effort in empowering student potential in entrepreneurship. Seeing this condition, we propose processing rejected Manalagi apples as an empowerment solution, considering that these apples are abundant in Malang Regency, especially during the main harvest. Rejected quality apples, which reach 10-20% of the harvest, are often wasted. In fact, green apples have health benefits, especially for diabetics, by helping to regulate blood sugar levels and increasing metabolism. Through this community service program, we process rejected apples into high-value products, such as syrup, jam, and pudding. This activity also involves children from the Sunan Ampel Orphanage as production partners. This is done to provide them with entrepreneurial skills and overcome the problem of high youth unemployment, while accelerating the physical, mental, and social-emotional development of the children in the orphanage. With this approach, we hope to increase community income, create job opportunities, and produce new, innovative entrepreneurs who will later be able to become independent entrepreneurs.